An Analysis of Ten Companies’ Financial Performance in the Indian Corporate Sector - Pinal Patel; Dr. R. Shridhar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The corporate sector is the backbone of the Indian economy since it offers a vital, effective, and planned framework for the growth of both the industrial and non-industrial sectors of the economy. As of June 30, 2018, there were 11,89,826 active corporations, according to the ministry of corporate affairs. As of June 30, 1,390 companies were classed as dormant, while 5.43 lakh of the 17.79 lakh registered companies in India were closed. A company’s ability to earn money and employ assets from its principal mode of business is measured subjectively by its financial performance. The 10 Indian corporations’ financial performance is examined in this study paper. Over a two-year period, the variables pertaining to sales, profit after tax, market capitalization, change in profit, and revenue of the companies were analyzed. The companies covered by this study include Tata Motors Ltd., Bharat Petroleum Corporation Ltd., Hindustan Petroleum Corporation Ltd., State Bank of India, Reliance Industries Ltd., and Indian Oil Corporation Ltd. Coal India Ltd., Tata Steel Ltd., and Rajesh Export Ltd. According to the study, all of these businesses did well in terms of sales and profit after taxes, with the exception of Tata Motors Ltd., which lost money after taxes totaling Rs. 28826.23 crores during the 2018–2019 fiscal year despite having revenue of Rs. 305280.69 crores and a market capitalization of Rs. 48588.33 crores. Sales for the company increased from 2018 to 2019 since RIL ranked first in the 2019 fiscal year and second in the previous year. We discovered that the SBI’s performance was poor in 2018 as a result of the combination of its affiliated state banks; the bank’s income only climbed by 7.88 percent. From 2018 to 2019, Tata Motors Ltd.’s revenue and profit after taxes were 2.06% and PL, respectively. "PL" stands for profit in 2018 and loss in the next fiscal year. We draw the conclusion that during the study, Tata Motors, BPCL, and HPCl’s performance somewhat declined, which helped to increase sales and control costs. The management of the company should develop creative ways to increase customer value in the ever-evolving, cutthroat business climate. This will increase returns on investment and fortify the company’s finances.